Sistem SCADA berbasis Internet of Things - Idris, Hernan S; Saputra, Agung; Mulyadi, Indra Hardian (Journal of Applied Electrical Engineering, 2023)
Supervisory Control and Data Acquisition (SCADA) control on PLCs generally cannot be controlled by IoT via the IoT platform. Therefore, in this study, a PLC-based SCADA control was created which will be displayed on the web. The PLC used in this system is Schneider TM241CE24R, and controlling the IoT system by utilizing the ESP32 module as an intermediary. For communication between the ESP32 and the PLC and Power meter devices, the Modbus RTU communication protokol is used where data will be processed on ESP32 before sending data to the server. The SCADA monitoring system uses the web with Node.JS as the server side and Express.JS as the framework, and uses Message Queuing Telemetry Transport (MQTT) as the communication protokol between ESP32 and the server. System testing consists of communication between the PLC and the Power meter to ESP32, ESP32 communication to Node.JS, testing the delay in sending data from the web to the PLC device, testing the delay in sending PLC to the web and testing packet loss in sending data using the Wireshark software. The results of this research can make it easier for SCADA systeMS that use RS485 as a communication that can be monitored in realtime, the average delay response time on PLC and Power meter communication devices to the web is 0.3 seconds when connected to the good internet and the average delay response time of 0.5-1 second when the internet is bad and this system can be accessed anywhere as long as this device is connected to the internet.